Comparison of Charge-Coupled Devices and Photostimulable Phosphor Storage Plates for Detection of Vertical Root Fractures in Endodontically Treated Teeth: An In Vitro Study - Sakhdari, Shirin; Mehrvarzfar, Peyman; Safari, Somayyeh; Pazhutan, Maryam; Kharazifard, Mohammad Javad (Journal of Dental School, 2019)
Objective: Vertical root fracture (VRF) is among the most common causes of endodontic treatment failures. This study aims to compare charge-coupled devices (CCD) and photostimulable phosphor plates (PSP) for detection of vertical root fractures in endodontically treated teeth. Methods: In this diagnostic in vitro study, 40 maxillary anterior teeth were selected and after preparation and root canal filling, their crowns were cut 2mm above the cementoenamel junction (CEJ). The teeth were embedded in a piece of dried bone and radiographed using CCD and PSP with equal geometry at zero and 15° horizontal angles. VRFs were then induced and the fractured fragments were reattached. The teeth were radiographed again. Three observers evaluated the radiographs for detection of fracture line. Data were analyzed using the Proportion test and Wilcoxon’s Signed Ranks test. Results: No significant difference was found between the two sensors in detection of VRFs [p-value (complete)= 0.592, p-value (absolute)= 1]. The sensitivity of the two sensors for detection of buccolingual and mesiodistal fractures was not significantly different [p-value BL (absolute)= 0.109, p-value BL (complete) 0.180] [p-value MD (complete)=0.593, p-value MD (absolute)= 0.102]. The sensitivity of both sensors for detection of buccolingual fracture was higher than for mesiodistal fractures (p<0.001). Conclusion: CCD and PSP had equal efficacy for detection of VRFs in endodontically treated teeth.